Efficacy of nebulized hypertonic saline versus normal saline and salbutamol in treating acute bronchiolitis in a tertiary hospital: a randomized control trial - Hossain, Rumi Myedull; Shams, Samina; Kader, M. Abdul; Pervez, Mehdi; Bhuiyan, M. Faisal Hasan; Hasan, M. Mahmudul; Mollah, M. Abid Hossain (International Journal of Contemporary Pediatrics, 2022)
Background: Bronchiolitis is an acute seditious lesion of the lower respiratory tract. Further, than 70 cases are caused by a respiratory syncytial virus (RSV); other less common pathogens include parainfluenza, influenza, rhinovirus, adenovirus, mortal metapneumovirus, mortal Boca contagion and mycoplasma pneumonae. The aim of the study was to evaluate the efficacy of nebulized hypertonic saline in children with acute bronchiolitis in the improvement of clinical features and decreasing length of hospital stay. Methods: The study was a randomized control trial carried out in the department of paediatrics, Dhaka medical college hospital (DMCH), Dhaka between January to December 2013. A total of 100 children from 1 month to 24 months of age irrespective of sex with clinical presentation of bronchiolitis admitted in the paediatric wards of DMCH were included in the study and were randomly assigned to either 4 ml 3% hypertonic saline nebulization (group I=50) or to 4 ml normal saline and 0.4 ml salbutamol respiratory solution nebulization (group II=50). The therapy was repeated 8 hours every day for 120 hours. Results: The clinical severity scores (CS) based on respiratory rate, wheezing, chest retraction and general conditions at baseline on the first day of treatment were 9.0±1.0 in group I and 9.3±1.8 in group II (not significant). The study demonstrated that clinical severity score improved by three days but the improvement was more significant in children who received nebulized hypertonic saline (1.7±1.2) compared to those who received nebulized normal saline and salbutamol (3.5±1.8). The cases of group I required a shorter duration of oxygen therapy compared to those of group II (15±6.0 hours versus 26.4±5.4 hours; p<0.05). Forty-seven patients (94%) were discharged within 72 hours of treatment in group I and 29 patients (58%) in group II. The length of hospital stay was shorter in group I 58.1±22.0 hours compared to group II 74.7±27.2 hours. None of the cases of any group encountered any side effects due to study drugs. Conclusions: 3% hypertonic saline nebulization significantly reduces clinical severity and length of hospital stay of children suffering from acute bronchiolitis in comparison to those treated by normal saline and salbutamol nebulization.